COPULA MODELING IN ANALYSIS OF DEPENDENCY OF OIL PALM PRODUCTION AND RAINFALL - Dadan Kusnandar; Naomi Nessyana Debataraja; Shantika Marthal (Indonesian Journal of Physics and Nuclear Applications, 2018)
Copula is a method that examines the relationship pattern between variables. Copula is characterized as a nonparametric method with several benefits, i.e., it is independent of the assumption of the distribution, accommodates nonlinear relationship among variables, and is convenient in building joint distribution. This study investigates the relationship and prediction analysis using the copula approach. The method is applied to the monthly data of oil palm production and the amount of rainfall. The results show that the model of Frank Copula is the best model for rainfall and oil palm production relationship.